Clodronate-loaded liposomal and fibroblast-derived exosomal hybrid system for enhanced drug delivery to pulmonary fibrosis. (April 2021) - Sun, Lingna; Fan, Mingrui; Huang, Dong; Li, Bingqin; Xu, Ruoting; Gao, Feng; Chen, Yanzuo
Abstract: Pulmonary fibrosis is a rapidly progressive and fatal fibrotic lung disease with high mortality and morbidity. However, pulmonary fibrosis therapy in the clinic has been limited by poor selectivity and inefficiency of drug delivery to fibroblasts. Herein, a clodronate (CLD)-loaded liposome and fibroblast-derived exosome (EL-CLD) hybrid drug delivery system with non-specific phagocytosis inhibition and fibroblast homing properties, was designed for the treatment of pulmonary fibrosis. EL-CLD effectively depleted Kupffer cells via apoptosis by passive targeting after intravenous injection, and thus significantly reduced accumulation in the liver. Notably, the EL-CLD hybrid system preferentially accumulated in the fibrotic lung, and significantly increased penetration inside pulmonary fibrotic tissue by targeted delivery due to the specific affinity for fibroblasts of the homologous exosome. Nintedanib (NIN), an anti-fibrotic agent used to treat pulmonary fibrosis, was loaded in the EL-CLD system, and achieved a remarkable improvement in curative effects. The enhanced therapeutic efficacy of NIN was a result of enhanced pulmonary fibrotic tissue accumulation and delivery, combined with a diminished macrophage-induced inflammatory response. Hence, the EL-CLD hybrid system acts as an efficient carrier for pulmonary anti-fibrotic drug delivery and should be developed as an efficient fibroblast specific therapy.